2016
DOI: 10.1007/s10511-016-9449-2
|View full text |Cite
|
Sign up to set email alerts
|

The N/O Ratio in Early B-Type Main Sequence Stars as an Indicator of Their Evolution

Abstract: It is shown that, in the case of early B-type main-sequence stars, of the three ratios N/C, C/O, and N/O which are regarded as indicators of stellar evolution, the ratio N/O is more reliable since it seems to be insensitive to overionization of the NII and OII ions. On the other hand, the N/C and C/O ratios, which include carbon, may contain systematic errors for stars with T eff > 18500 K because of neglected overionization of CII ions. The ratio N/O is studied in the atmospheres of 46 early main-sequence B s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As an example of good agreement with these results, one may indicate an analysis of the N/O ratio for 46 early B-type MS stars (Lyubimkov 2016(Lyubimkov , 2018. It was found that most of the stars near the MS termination (82 %) show the relatively low values [N/O] < = 0.3; from the viewpoint of the theory (Georgy et al 2013), these stars had the low initial rotational velocities V 0 from 0 to 130 km/s.…”
Section: Discussionmentioning
confidence: 58%
“…As an example of good agreement with these results, one may indicate an analysis of the N/O ratio for 46 early B-type MS stars (Lyubimkov 2016(Lyubimkov , 2018. It was found that most of the stars near the MS termination (82 %) show the relatively low values [N/O] < = 0.3; from the viewpoint of the theory (Georgy et al 2013), these stars had the low initial rotational velocities V 0 from 0 to 130 km/s.…”
Section: Discussionmentioning
confidence: 58%
“…Data from a recent analysis of the N/O ratio in the atmospheres of 46 early MS B-stars [13] can also serve as confirmation of this effect. N/O can be regarded as one of the indicators of stellar evolution.…”
Section: The Initial Rotation Velocity V 0 and The Abundance Of Lithiummentioning
confidence: 84%
“…Strictly speaking, a comparison with models of rotating stars implies that they have V 0 < 100km/s. Only when V 0 = 200-300 km/s are elevated values of [N/O] = 0.4 -0.8 observed at the end of the MS, but there are few stars of this kind [13].…”
Section: The Initial Rotation Velocity V 0 and The Abundance Of Lithiummentioning
confidence: 97%
See 1 more Smart Citation